Atomic scale characterization of SiO2/4H-SiC interfaces in MOSFETs devices. (November 2015) - Beltrán, A.M.; Duguay, S.; Strenger, C.; Bauer, A.J.; Cristiano, F.; Schamm-Chardon, S.
Abstract: The breakthrough of 4H-SiC MOSFETs is stemmed mainly due to the mobility degradation in their channel in spite of the good physical intrinsic material properties. Here, two different n -channel 4H-SiC MOSFETs are characterized in order to analyze the elemental composition at the SiC/SiO2 interface and its relationship to their electrical properties. Elemental distribution analyses performed by EELS reveal the existence of a transition layer between the SiC and the SiO2 regions of the same width for both MOSFETs despite a factor of nearly two between their electron mobility. Additional 3D compositional mapping by atom probe tomography corroborates these results, particularly the absence of an anomalous carbon distribution around the SiC/SiO2 interface. Highlights: Mobility degradation in 4H-SiC MOSFETs. Structural analysis by HRTEM images and compositional distribution by STEM–EELS. Three-dimensional characterization by atom probe tomography (APT). No C anomalous distribution at the interface; instead a smooth transition layer. Roughness at the interface SiC/SiO2 .